Can alteration in host odor blends change the olfactory preferences in Spodoptera littoralis? - Olovsson, Hanna (SLU/Dept. of Plant Breeding (from 130101), 2017)
Gustatory and olfactory stimuli have been shown to induce feeding preferences in generalist phytophagous insect species. Generalists have to process a lot of information while performing host selection and it has been suggested that this may be a limitation, while it makes the host detection slower than for specialist species that process a lower amount of information. Experiences from earlier stages may therefore work as a way for generalists to make the processing of information faster (Anderson et al., 2013). Webster et al. (2010) showed, in an experiment where the insect had been exposed to volatiles alone and in combination, that the insect responded stronger to a blend than to single compounds. By changing the blend it may therefore be possible to disturb the host recognition. In this study the Egyptian cotton leaf worm Spodoptera littoralis was used as model species. The aim of the study was to study interactions between olfactory preferences and host odor blends by manipulating the preferences of S. littoralis through prior experience, and by artificial manipulation of odor blends. The study was targeted towards a specific set of questions: 1) Will larvae fed on cowpea develop a preference for cowpea when presented two choices? 2) Will larvae exposed to the odor of cotton plants develop a preference for cotton over cowpea? 3) Will larvae exposed to altered forms of cotton plant odor behave like larvae exposed to cotton odor or will the detection mechanism of host detection be disturbed? 4) Will adult female Spodoptera littoralis prefer the same plant species as they preferred as larvae? The larvae were tested in a y-tube olfactometer for dual choices and the adults were tested for oviposition preference. This study shows that larvae of S. littoralis are able to make a choice when presented two alternatives. A tendency for an induced feeding behavior prior to earlier experiences could be seen. Larvae exposed to odors did not show a preference prior to earlier experiences and the adults did not show any preference in their oviposition choices.